Implementation of Circular Economy Concepts Through Eco-Enzyme Production in the Management of Food Left Waste in Mambal Village - PURNAMAWATI, Ida Ayu Putu Santi; LAKSMI, Putu Ayu Sita; SURIANI, Ni Nyoman (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2024)
The waste problem is a severe issue in Indonesia, including on the island of Bali, which is famous for its natural beauty. MambalVillage in Badung Regency is the focus of the  Real Work Lecture-Community Empowerment by Students (KKN-PMM) program from Warmadewa University. In this program, students attempt to overcome the problem of food waste by introducing the concept of a circulareconomy  through  the  production  of  eco-enzymes.  Eco-enzymes  can  be  made from  organic  waste,  especially  food  waste.  Its  use  follows  circular  economy principles by converting  waste  into value-added resources. Through a series  of activities, including collecting raw materials, holding demonstrations on making eco-enzymes,   the   KKN-PMM program succeeded in providing a practical solution to the food waste problem in Mambal Village. Active community participation, Apart from that, this  program  also  integrates  various  fields  of  science,  such  as  law,  health, engineering,   administration   and   economics,   to   improve   prosperity   and sustainability at the local level. Thus, the KKN-PMM program in Mambal Village is  a  concrete  example  of  applyingthe  circular  economy  concept  to  overcoming environmental problems. Through collaboration between students and the local community, this program provides practical benefits and creates harmonious and mutually  beneficial  relationships.  The  hope  is  that  thiseffort  can  inspire  other regions  to  face  similar  challenges  in  waste  management,  which  is  in  line  with circular   economy   principles   that   minimize   waste   and   maximize   resource utilization.